Analisis Perbandingan Konsep Kebangkitan Roh dan Kebahagiaan Akhirat Dalam Pemikiran Ibn Sina dan Al-Ghazali Menurut Perspektif Psikospiritual Islam: Comparative Analysis of The Concepts of The Soul’s Resurrection and Hereafter Happiness in The Thought of Ibn Sina and Al-Ghazali from The Perspective of Islamic Psychospirituality - Mohd Akib, Mohd Manawi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
The discourse on the soul is an important topic in Islamic psychology, particularly in the works of al-Kindi, al-Farabi, Ibn Sina, al-Ghazali, and Fakhr al-Din al-Razi. This theme raises two major issues: the concept of soul resuscitation and happiness in the hereafter. Understanding these principles is important for forming an individual's thought, judgment, and behavior habits. Materialistic inclinations in modern civilization have resulted in a variety of moral issues, including selfishness, dishonesty, envy, and a hedonistic culture that prioritizes worldly wealth and pleasure over moral and spiritual ideals. Thus, this article highlights these two issues as defined by two influential Muslim psychologists, Ibn Sina and al-Ghazali, using a qualitative method based on content analysis of their works to assess the continuity of their perspectives on the subject. The study discovers a significant difference between the two thinkers about the resurrection of the soul in the afterlife: Ibn Sina believes that only the soul is resurrected, whereas al-Ghazali believes in the resurrection of both the soul and the body. Nonetheless, both concur that the utmost felicity of the soul in the afterlife is gained through intellectual or spiritual delight, which occurs when the intellect's potential is utilized to acquire real knowledge, resulting in piety and cultivation of noble character. This aligns with the Islamic psychospiritual framework, which emphasises faith in God Almighty and the Hereafter as the basis for spiritual purification; worship as a means of strengthening one’s relationship with God and guiding the intellect toward its proper use; and character (akhlaq) as the manifestation of spiritual intelligence derived from knowledge that leads to piety.